Differences in eating habits, physical activity, and sleep patterns among high school students and their parents before and during COVID-19 pandemic - Shoug Alashmali (Frontiers Media S.A., 2024)
IntroductionThe recent COVID-19 pandemic has profoundly disrupted the eating and lifestyle habits among populations, especially among younger populations who are more prone to unhealthy dietary behaviours. However, current knowledge related to eating and lifestyle patterns, especially physical activity and sleep among different generations is limited. Our study sought to understand the eating habits, physical activity, and sleep behaviours among high school students compared to their parents in Saudi Arabia, before and during the COVID-19 pandemic.MethodsThis study was conducted in public high schools in Jeddah, Saudi Arabia (n = 8 schools), spanning from September 2021 to April 2022. Data were collected using an online questionnaire, distributed to all students and their parents (n = 516) in these schools.ResultsDuring the pandemic, parents (46.4%) showed a heightened interest in health and nutrition compared to students (32.7%, p = 0.001). Food preferences changed for 58.1% of participants; 70.0% of parents and 36.7% of students opted for homemade food (p < 0.001). Unhealthy behaviours like eating out were more common in students. Weight varied by 74.0% during COVID-19, with more parents (41.4%) gaining weight than students (31.6%, p = 0.018). Physical activity dropped more for parents (42.1%) than students (23.9%), though 30.7 and 31.6% reported increases, respectively (p < 0.001). Regardless of the pandemic, students were more likely to sleep later compared to parents (58.0% vs. 41.4%; p < 0.001), while parents were more prone to waking up earlier compared to students (81.4% vs. 67.3%, p = 0.002).DiscussionThe findings underscore the varied pandemic impact on eating habits and physical activity between students and parents. Tailored interventions are vital for promoting healthier choices during health crises.